Government at a Glance 2013. - (:unkn) unknown (My University, 2013)
Government at a Glance 2013 provides readers with a dashboard of key indicators assembled with the goal of contributing to the analysis and international comparison of public sector performance. The financial and economic crisis and its aftermath have led many OECD governments to implement structural adjustment plans to restore the health of their public finances. However, trust in governments has declined considerably, as citizens' growing expectations have been hard to address with limited government resources. Between 2007 and 2012, confidence in national governments declined from 45% to 40% on average, making it difficult for national authorities to mobilise support for necessary reforms. A new approach to public governance is needed if governments are to meet citizens' expectations with the limited means at hand. This approach should be built around creating strategic capacity, strong institutions, effective instruments and processes, and clear measurable outcomes. The indicators presented in Government at a Glance 2013 show how far OECD countries have progressed towards developing that strategic state.
Keywords: Haushaltswesen; Finanzpolitik; Staat; Verschuldung; Ländervergleich; Öffentlicher Sektor; Reformfähigkeit; Internationaler Vergleich